Prevalence and clinical correlates of chronic obstructive pulmonary disease in heart failure patients: a cross-sectional study in China - Zhu, Ailing; Hu, Manman; Ge, Dehai; Zhang, Xiujian; Zhang, Jinfeng; Wang, Yangchun; Yao, Xin; Liu, Junjun (Frontiers in Medicine, 2025)
BackgroundDespite chronic obstructive pulmonary disease’s (COPD)'s prevalence in the general populace, its incidence in heart failure (HF) patients is understudied. This study aimed to assess COPD prevalence and clinical associations in Chinese HF patients.MethodsFrom the Chinese Heart Failure Study, demographic and clinical details of 2008 HF patients were analyzed. Divided into 233 COPD cases and 1775 non-COPD controls, a multivariable logistic regression identified factors linked to COPD onset in HF, with thorough examination of intergroup clinical differences.ResultsThe incidence of COPD in HF individuals was 11.60% (233/2008). The COPD subgroup featured a higher ratio of individuals over 60 and males, alongside lower systolic blood pressure (SBP), body mass index (BMI), higher Charlson Comorbidity Index (CCI) scores, and increased PaCO₂ levels (p < 0.05). Type II respiratory failure and right ventricular dysfunction (RVD) were more prevalent in the COPD subgroup (p < 0.001). Binary logistic regression, after adjustments, indicated positive associations between COPD and age over 60 (OR = 3.831, 95%CI: 1.085–13.526, p = 0.037), male sex (OR = 1.587, 95%CI: 1.032–2.441, p = 0.036), higher CCI (OR = 2.214, 95%CI: 1.796–2.729, p < 0.001), elevated PaCO2 (OR = 1.035, 95%CI: 1.015–1.055, p < 0.001), and RVD (OR = 0.605, 95%CI: 0.119–3.063, p = 0.544). Inversely, higher SBP (OR = 0.990, 95%CI: 0.982–0.998, p = 0.020) and log (triglycerides) (OR = 0.183, 95%CI: 0.064–0.552, p = 0.002) were negatively correlated with COPD in HF patients.ConclusionIn a large cohort of Chinese Heart Failure (HF) patients, our study revealed a notable COPD prevalence. Key risk factors included age, sex, elevated PaCO2, CCI score, and right heart failure, while higher SBP and triglyceride levels offered protection. These insights lay groundwork for probing disease mechanisms and therapeutic approaches.